Tortugas continentales (Pleurodira: Chelidae) en la Formación Roca (Daniano), provincia de Río Negro, Argentina (Ameghiniana, 2009)
Roca Formation is a stratigraphic succession of marine and continental sedimentsthat belongs to Malargüe Group, which was deposited from the Late Campanian to the Danian in theNeuquén Basin, western Argentina. Fossil vertebrates recovered at different outcroppings of this lithostratigraphicunit correspond to marine taxa. The turtle material studied here was collected from the lowersection of Roca Formation (Maastrichtian?-Danian) in northeastern Lago Pelegrini (38º 40’ 06’’S, 67º 52’ 02’’O), Rio Negro Province. Remains of carapace and plastron of continental turtles were assigned to indeterminatechelid pleurodires and to Yaminuechelys cf. maior (Staesche, 1929). This record of chelid turtles inRoca Formation confirms the existence of marine paleoenvironments with continental influence and representsthe first record of Danian continental vertebrates in the Neuquén Basin.